METHODOLOGY FOR THE IDENTIFICATION OF INTERNAL AND EXTERNAL COMPETENCY RELATIONS IN THE FIELD OF INTELLECTUAL PROPERTY PROTECTION - Zajac, Jozef; Hatala, Michal; Olexa, Lubomir; Zajac, Jan (European Scientific Journal, ESJ, 2014)
The article presents the experience with the introduction of “System of Quality Management” in TU in Kosice (TUKE) according to ISO 9001. It describes the system of managing quality including all competency relations and the philosophy of implementation of the system into real conditions of research and educational institution in terms of intellectual property rights.